Description of three new arctic bramble cultivars and proposal for cultivar identification - PIRINEN, H.; DALMAN, P.; KÄRENLAMPI, S. (Agricultural and Food Science, 1998)
Morphological and yield differences between five arctic bramble (Rubus arcticus L.) strains and the cultivars Pima and Mespi were studied at two locations during the growing season 1994. Morphological observations and measurements were made on canes, leaves, flowers and berries, adapting the UPOV (Union pour la Protection des Obtentions Vegetales) descriptions for strawberry and raspberry. The plants were also compared with the aid of random amplified polymorphic DNA analysis. Apart from DNA, the most important distinctive characteristic was yield. Characteristics of the flowers, leaves and berries, such as number, size, shape and colour were used to differentiate between the arctic bramble genotypes. The yield of three new cultivars, named Marika, Muuruska and Elpee, was greater than that of Pima or Mespi. The yield of 'Marika' and 'Elpee' was 2,4-times and that of 'Muuruska' 1,9-times that of 'Pima' or 'Mespi'. Based on distinctive morphological characteristics, guidelines for the description of arctic bramble are proposed. This description may also be used for hybrids of arctic bramble with Rubus stellatus Sm., i.e. Rubus arcticus L. nothosubsp. stellarcticus G. Larsson. ;